Analisis kandungan vitamin c pada kandungan buah enau ( a. pinnata ) di desa nekmese - Felyxcia Cyndi Claudia Rianghepat; Andriani Rafael; Apriliana Ballo (Indigenous Biologi : Jurnal Pendidikan dan Sains Biologi, 2021)
ABSTRACTPalm trees (Arenga pinnata (wurmb.) Merr.) Are plantation crops that have the potential to be cultivated in the future, because they have high economic value and are prospective for commercial development given the diverse uses. Enau is a plant that was developed from generation to generation on Timor Island. Communities in the village of Nekmese still manage traditional palm trees. Vitamin C or ascorbic acid is one of the vitamins made from hexose derivatives which is water soluble and easily oxidized. The purpose of this study was to determine the vitamin C content of palm meat (A. pinnata). This research was conducted in May 2019 at the TPH Laboratory of the State Polytechnic of Kupang. Determination of vitamin C content in the sample is determined by titration using a solution of iodine. From the results of the study showed that the content of vitamin C in the flesh of the most palm fruit is found at a temperature of 5 ° C and 10 ° C while the content of vitamin C which is the least amount is at a temperature of 15 ° C.Keywords: palm plant and vitamin C